Microelectromechanical Systems (MEMS) Heatuator - Zaliman, Sauli, Prof. Madya; Hasnizah, Aris; Razaidi, Hussin; Mohd Hafiz, Ismail; Rizalfande, Che Ismail (International Exhibition of Inventions, 2010)
Assoc. Prof. Zaliman Sauli and his team won silver at 35th International Exhibition of Inventions of Geneva 2007, 18th - 22nd April 2007 at Palexpo Hall 7, Geneva, Switzerland.